Akal bertingkat dan taksonomi Bloom: Pengembangan pendidikan Islam berorientasi HOTS - Munzir; Suyadi (Tawazun: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the concept of multilevel reasoning and its correlation with Bloom’s taxonomy on the development of Higher Order Thinking Skill (HOTS)-oriented Islamic education. This research approach is library research using the content analysis method. The source of the data for this research is literature that comes from books and journals in the field of Islamic religious education, multilevel sense, and bloom’s taxonomy. Data collection is done by tracing related references, both manually and digitally. The collected data is then displayed, reduced, and constructed into a new concept that is complete and fresh. This finding is different because there is an interdisciplinary science between the development of Islamic education and the correlation of multilevel reasoning with Bloom’s taxonomy. The results of this study indicate that the hierarchical sense of stratification has a historical correlation with Bloom’s taxonomy. It is identified as semiotic or the same meaning. Therefore, multilevel reasoning and Bloom’s taxonomy have relevance in the development of Islamic religious education that is HOTS-oriented, especially in the learning stages. For example, the hierarchy of acquisition of reason has the same meaning as being creative. Abstrak Penelitian ini bertujuan untuk menganalisis konsep akal bertingkat dan korelasinya dengan taksonomi Bloom pada pengembangan pendidikan Islam berorientasi HOTS. Pendekatan penelitian ini adalah penelitian kepustakaan (library research) dengan menggunakan metode analisis isi (content analysis). Sumber data penelitian ini adalah literatur yang berasal dari buku maupun jurnal dibidang pendidikan agama Islam akal bertingkat dan taksonomi bloom. Pengumpulan data dilakukan dengan menelusuri referensi terkait, baik secara manual maupun digital. Data-data yang terkumpul kemudian didisplay, direduksi dan dikonstruksi menjadi konsep baru yang utuh dan juga fresh. Temuan ini berbeda karena terdapat interdisipliner ilmu antara pengembangan pendidikan Islam dan korelasi akal bertingkat dengan taksonomi bloom. Hasil penelitian ini menunjukkan bahwa hierarki akal bertingkat memiliki korelasi historis dengan taksonomi bloom. Hal ini diidentifikasikan secara semiotik atau makna yang sama. Oleh karena itu, akal bertingkat dan taksonomi bloom memiliki relevansi dalam pengembangan pendidikan agama Islam berorientasi HOTS terutama dalam tahap-tahap pembelajaran. Misalnya hierarki akal perolehan memiliki makna yang sama dengan berkreasi.